2006
DOI: 10.1177/1066896906293348
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation Between the Tumor Necrosis and Renal Artery Changes in Renal Cell Carcinoma

Abstract: Necrosis, cysts, hemorrhage, and calcification represent common findings in renal cell carcinoma. Different lesions, including arteriosclerosis or fibromuscular dysplasia, or both, may involve the main renal artery. This study analyzed the relationship between the presence and extent of necrosis in renal cell carcinoma with renal artery changes in a consecutive series of 112 patients (71 men, 41 women) with mean renal cell carcinoma of 7.7 cm (range, 2 to 20 cm). Necrosis was seen macroscopically and confirmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 25 publications
0
6
1
Order By: Relevance
“…Although the present as well as previous studies [11,20] pointed to a high rate of renal artery lesions in RCC patients, we found no significant differences in renal artery diameter or media layer thickness between renal arteries without changes and those with FMD or atherosclerotic lesions. This finding was not unexpected since our study of the control group as well as other studies [4,12,16,19] showed renal artery changes to be mostly segmental, with only a small part of renal artery being available for sampling and histological examination after radical nephrectomy due to RCC.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…Although the present as well as previous studies [11,20] pointed to a high rate of renal artery lesions in RCC patients, we found no significant differences in renal artery diameter or media layer thickness between renal arteries without changes and those with FMD or atherosclerotic lesions. This finding was not unexpected since our study of the control group as well as other studies [4,12,16,19] showed renal artery changes to be mostly segmental, with only a small part of renal artery being available for sampling and histological examination after radical nephrectomy due to RCC.…”
Section: Discussioncontrasting
confidence: 54%
“…However, the exact pathogenesis of tumor necrosis as well as the cause and nature of renal artery changes and the possible impact Tomic et al 10 on tumor necrosis have not yet been fully clarified [11,17]. We observed an increase in media layer thickness in the group of RCC patients, with the presence and increased extent of tumor necrosis (no necrosis: less than 50% necrosis: more that 50% necrosis= 499.4 µm: 531.4 µm: 657.3 µm), however, the differences were not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence and extent of tumour necrosis were defined from macroscopic and microscopic findings as in similar studies on RCC and on soft-tissue tumour grading [16,17,19]. The degree of the necrosis was designated as absent (0), less than 50% tumour necrosis (I) or more than 50% tumour necrosis (II).…”
Section: Methodsmentioning
confidence: 99%
“…Pathological renal artery changes are found in a high percentage of patients with RCC [15,16]. The results of one morphometric study showed that renal arteries in a group of patients with RCC have a thicker tunica media layer than those in the control group (without RCC) [17].…”
Section: Introductionmentioning
confidence: 96%